The International Classification of Functioning, Disability, and Health (ICF) as a community participation model for people with multiple sclerosis: A hierarchical regression analysis. Issue 2 (3rd December 2020) - Pfaller, Joseph; Chan, Fong; Iwanaga, Kanako; Wu, Jia-Rung; Rumrill, Stuart; Chen, Xiangli; Lee, Deborah; Berven, Norman L.
Abstract: Multiple sclerosis (MS) is a central nervous system disorder that impacts more than 400, 000 people in the U.S. The disease results in multiple functional impairments that are diverse and varied across individuals. Additonally, MS has a profound impact on community participation which, like other rehabilitation outcomes, cannot be explained on the basis of functional limitations alone. The purpose of this study was to develop and evaluate a model of community participation for people living with MS using the World Health Organization (WHO) International Classification of Functioning, Disability, and Health ( ICF ) framework. The model focused on the roles that personal factors have as predictors of community participation, while also serving as mediators and moderators for the relationship between activity limitation and participation. Results from the hierarchical regression analysis indicated that demographic characteristics (i.e. MS type), personal factors (i.e. core self-evaluations (CSE), MS self-management, resilience, and social skills), and activity limitations accounted for 64% of the variance in participation. Further, mediation analysis indicated that CSE mediated the relationship between activity limitation and community participation. Finally, moderation analysis indicated an interaction effect between educational attainment and MS self-management. Implications for future research in rehabilitation and clinical application are discussed.